Systematic Literature Review: Security Gap Detection On Websites Using Owasp Zap - Putra, Fauzan Prasetyo Eka; Ubaidi, Ubaidi; Hamzah, Amir; Pramadi, Walid Agel; Nuraini, Alief (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
This research highlights the detection of security vulnerabilities on websites using OWASP ZAP, a highly regarded open-source web security testing tool. Through a comprehensive literature review approach and systematic research methodology, this research emphasizes the urgency of addressing the ever-evolving security threats in web systems. Web security is a crucial aspect of information technology as more and more sensitive data is transmitted through web applications. OWASP ZAP, recognized for its reliability in identifying various security holes, was used to evaluate its effectiveness and efficiency in detecting vulnerabilities in web applications. This tool assists developers and security researchers in finding and fixing weaknesses that could be exploited by attackers. The results of the study show that OWASP ZAP is not only effective in identifying vulnerabilities such as SQL Injection, XSS (Cross-Site Scripting), and misconfiguration but also provides practical solutions to strengthen overall web security. Additionally, this research identifies several challenges faced when using OWASP ZAP and offers recommendations to address these issues. This study makes a significant contribution towards a better understanding of web security and offers recommendations for the implementation of better security testing tools in web development environments. Consequently, this research encourages the adoption of more proactive and systematic security practices in web application development.